Cost-effectiveness of internet-based cognitive-behavioral treatment for bulimia nervosa: results of a randomized controlled trial - Watson, Hunna; Moessner, Markus; Zimmer, Benjamin (The journal of clinical psychiatry, 2018)
From The Journal of Clinical Psychiatry: Cognitive-behavioral therapy tailored for bulimia nervosa (CBT-BN) is the best-supported treatment for this eating disorder, but the lack of highly trained practitioners and the limited distribution of this treatment limit its accessibility. Read this article to learn about the cost-effectiveness and viability of an Internet-based version of CBT-BN.